2021
DOI: 10.38079/igusabder.894802
|View full text |Cite
|
Sign up to set email alerts
|

Hemşirelik Öğrencilerinin Doğrudan Bakım Uygulamalarına Ayırdıkları Süre ve Bakım Davranışları Algısının Belirlenmesi

Abstract: Araştırma, hemşirelik öğrencilerinin klinik uygulamalar sırasında doğrudan bakım uygulamalarına ayırdıkları zamanı ve öğrencilerin bakım davranışları algısını belirlemek amacıyla planlanmıştır.Yöntem: Araştırma tanımlayıcı tipte olup araştırmanın örneklemini bir vakıf üniversitesinin hemşirelik bölümünde öğrenim gören birinci sınıflar hariç toplam 80 öğrenci oluşturmuştur. Çalışmanın verileri "Klinik Uygulamada Hemşirelik Öğrencilerinin Aktivitelerini İzlem Formu" ve "Bakım Davranışları Ölçeği" ile toplanmıştı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…25 Similar to results of the present study, CBI scores were found to be high in different studies evaluating nursing students' caring behaviors. [26][27][28] In their study, Türk et al, evaluated the caring behaviors of the students as good. 29 When the subscales of CBI were examined, it was found in the present study that while the highest score was detected in the AS, the students had lower perceptions of KSs.…”
Section: Discussionmentioning
confidence: 99%
“…25 Similar to results of the present study, CBI scores were found to be high in different studies evaluating nursing students' caring behaviors. [26][27][28] In their study, Türk et al, evaluated the caring behaviors of the students as good. 29 When the subscales of CBI were examined, it was found in the present study that while the highest score was detected in the AS, the students had lower perceptions of KSs.…”
Section: Discussionmentioning
confidence: 99%